Optic neuritis and multiple sclerosis association - Matukynaitė , L.; Repšytė , G.; Liutkevičienė , R.; Balnytė, R. (Neurologijos seminarai, 2020)
Multiple sclerosis (MS) affects more than 2 million people worldwide. Lithuania has a high prevalence of multiple sclerosis. Optic neuritis (ON) occurs in 70% of patients with MS and it may be the initial presenting symptom in 25% of MS cases. Typical ON is often associated with MS due to the predominant inflammation and demyelination processes in the brain leading to axonal loss. The close relation between these two conditions in etiology and pathogenesis is a key to finding the earliest and the most accurate diagnostic possibilities, which is linked to a better understanding of the ongoing mechanisms. Moreover, it would undoubtedly allow to target treatment better which would result in more favourable outcomes for the patient. The development and application of ON diagnostic tests in confirming MS may be of particular significance in early diagnostic.
Keywords: optic neuritis; multiple sclerosis